Are Russian Students Ready to be Law-Abiding Taxpayers? Tax Morality Issues - Molodykh, Vladimir (Journal of Economic Sociology, 2019)
Tax morality is formed by the influence of social and psychology factors on society and has a great impact on the choice of deviating model behaviors by taxpayers. In this regard, tax evasion would be preferable to use in the behavioral economy instrumentarium, as it provides an opportunity to evaluate the effects of norms and behavior stereotypes formed in an individual choice. A survey among students from districts in the North-Caucasus Federal Region was held to estimate the level of tax morale. The results were analyzed using the z-test and the model formation of binary logistic regression. The research results have shown that interviewees are ready to evade tax legislation, even though most express a strong reluctance to attempt tax evasion. The main reasons for this are a low level of confidence in the legal system, the perception of the tax system as unfair, and the social norm distortions and the existence of entrenched behavioral stereotypes. With these stereotypes, tax evasion is not perceived as a grave violation. The existence of an unfair tax system, with a focus on retributive justice, leads to the violation of a psychological party to the agreement between the state and taxpayers as the appearance of “moral reasons” for the excuses of strategy choice for the tax evasion. In this regard, the integration of social norms, which regulate the interaction of the tax payers and the state, as well as a stimulating mechanism of loyalty enhancement on base of expanding frontiers in collaboration, into the system of tax administration will enable to create an alternative way of the rational choice for the tax players which will be not only morally praiseworthy but also economically justified.